Analisa Kualitas Layanan Pendaftaran Pasien Secara Online Pada RS Mekar Sari Bekasi Menggunakan Metode Servqual - Amalia Vernanda; Eva Zuraidah (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Good service quality is the main priority expected by patients or customers for the services to be received, and these virtues are used to meet the expectations of patients or customers. The problems that occur at the Mekar Sari Hospital Bekasi in online are not optimal due to the application of the Hidoku application used. The purpose of this study was to measure the quality of service that affects the level of patient or customer satisfaction with the servqual method. Measurement of patient satisfaction was done by looking for samples with the solving and obtaining 100 respondents. Measuring the level of patient satisfaction on the 5 dimensions of service quality service, namely reliability, responsiveness, assurance, tangible, and empathy and the results obtained are gaps or gaps in patient perceptions and expectations of -0160. From these gaps, they are grouped based on the IPA (Importance Performance Analysis) with the results that most must be maintained, namely the empathy -0.133, service attributes of Mekar Sari Hospital Bekasi which must be maintained by employees in understanding patient needs, assurance -0.155 including service attributes regarding data in online, reliability -0.157 attributes where the Hidoku application can be relied on by patients, responsiveness -0.175 attributes of online patient registration services that are responsive in answering patient questions and complaints, to dimensions that must be improved, namely the tangible (direct evidence). -0.180 service attributes in improving the quality of both offline and online for patients.